The complexity of the handgrip task modulates postural performance in older adults. - MAGALHÃES, GABRIELA V.; SCHEIDEGGER, NAYARA C. A.; RINALDI, NATALIA M. (Brazilian Journal of Motor Behavior, 2024)
BACKGROUND: The acts of reaching and grasping objects are involved in the performance of daily activities. There is a gap in the understanding of how the complexity of the grasping task associated with changes in the base of support influences postural control performance in the older population. AIM: To investigate the postural control performance of older people as they performed the grasping movement, with different levels of task difficulty and complexities of the base of support. METHOD: 15 young and 15 older adults participated. The participants stood on a force platform and performed: 1) Reaching a heavy object; 2) Reaching a light object in rigid and unstable base conditions. The variables analyzed were: area, mean velocity, and mean displacement amplitude of the center of pressure (COP). RESULTS: Older had higher COP velocity in the anteroposterior and mediolateral directions, as well as in the rigid and unstable bases. They also had a larger COP area in the rigid and unstable base of support, and for all gripping tasks. In both groups, the mean amplitude of COP displacement in the rigid base was higher while gripping a heavy object than while gripping a light object or performing a non-gripping task. CONCLUSION: Postural control in the older adults is mainly influenced by the difficulty of grasping tasks. It is possible to identify the postural control performance of the older while they grasp objects during daily activities and to assess how these activities disturb balance, which makes it possible to draw up guidelines to improve postural performance.